USM STRENGTHENING TIES WITH ASEAN UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, 3 March 2016 – Universiti Sains Malaysia (USM) continues to strengthen collaborative efforts with universities from the ASEAN countries.